Effect of Alpha-Lipoic Acid on Rat Ventricles and Atria under LPS-Induced Oxidative Stress - Beata Skibska; Anna Goraca; Agnieszka Skibska; Andrzej Stanczak (MDPI AG, 2022)
Alpha-lipoic acid (α-LA) is a disulfide compound and one of the most effective antioxidants. Many studies have indicated positive effects of α-LA in the prevention of pathologic conditions mediated by oxidative stress, such as cardiovascular diseases. However, the therapeutic potential of α-LA for the heart has not been explored with regards to the ventricles and atria. The aim of our study was to evaluate the effects of α-LA on oxidative stress parameters and inflammation in the ventricles and atria of the heart in rats under LPS-induced oxidative stress. Wistar rats were divided into 4 groups: I-control (received 2 doses of 0.2 mL of 0.9% NaCl i.v., 0.5 h apart); II-α-LA (received 0.2 mL of 0.9% NaCl and 0.5 h later received α-LA 60 mg/kg b.w. i.v.); III-lipopolysaccharide (LPS) (received 0.2 mL of 0.9% NaCl and 0.5 h later received LPS 30 mg/kg b.w. i.v.); and IV-LPS + LA (received LPS 30 mg/kg b.w. i.v. and 0.5 h later received α-LA 60 mg/kg b.w. i.v.). Five hours later, the rats were euthanized. The hearts were surgically removed and weighed to estimate heart edema. The ventricular and atrium tissue was isolated to measure levels of TNF-α, IL-6, superoxide dismutase (SOD), thiobarbituric acid reactive substances (TBARS), hydrogen peroxide (H2O2), total sulfhydryl groups (-SH), total glutathione (tGSH), reduced glutathione (GSH), glutathione disulfide (GSSG), and the GSH/GSSG ratio. LPS significantly increased TNF-α, IL-6, TBARS, and H2O2 levels and decreased SOD, -SH groups, tGSH, the GSH/GSSG ratio, and GSH levels in rat ventricles and atria while α-LA administered after the injection of LPS significantly decreased TNF-α, IL-6, TBARS, and H2O2 levels. α-LA also increased SOD and -SH group levels and ameliorated the glutathione redox status when compared to the LPS group. Our data suggest that α-LA administration 30 min after LPS infusion may effectively prevent inflammation and oxidative stress in the ventricles and atria.